2017
DOI: 10.1007/s11136-017-1734-y
|View full text |Cite
|
Sign up to set email alerts
|

Technology use and its association with health and depressive symptoms in older cancer survivors

Abstract: Investigation into reasons behind older cancer survivors' apparent low rates of engagement with ICT is warranted, particularly the examination of access as a potential barrier. Findings indicated that frequent use of communication technology was positively linked with mental and physical wellness. The nature of the relationships between communication technology use and physical and mental health merits further research, helping to determine whether community-based educational efforts to improve technology acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Interestingly, technophilia was also strongly associated with health status and depression after adjusting for possible confounders such as gender, age, education level, and cognitive function. One longitudinal study conducted by Cotten et al [ 44 ] and other studies [ 45 , 46 ] have found that use of the internet and ICTs in older individuals is associated with less depression and a better quality of life, and there is some evidence that this association is mediated by loneliness and social isolation [ 44 , 45 ]. In conclusion, these results highlight the potential barriers of interventions for the use of ICTs, including smartphones and tablets, to improve the quality of life of people with dementia/mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, technophilia was also strongly associated with health status and depression after adjusting for possible confounders such as gender, age, education level, and cognitive function. One longitudinal study conducted by Cotten et al [ 44 ] and other studies [ 45 , 46 ] have found that use of the internet and ICTs in older individuals is associated with less depression and a better quality of life, and there is some evidence that this association is mediated by loneliness and social isolation [ 44 , 45 ]. In conclusion, these results highlight the potential barriers of interventions for the use of ICTs, including smartphones and tablets, to improve the quality of life of people with dementia/mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The National Health and Aging Trends Study incorporates measures of frequency and types of Internet use (Kasper and Freedman, 2017). Most Internet-use-related secondary analyses using these data report cross-sectional findings (Choi and DiNitto, 2013; Elliot et al, 2014; Gell et al, 2015; Kim et al, 2016; Lee et al, 2017), with few reporting longitudinal results (Levine et al, 2017). A supplemental survey of a subsample of Health and Retirement Study (HRS) participants who report regular Internet use also explores being online in greater depth over six waves of data collection, although questions were added and deleted with each iteration, making longitudinal comparisons difficult (Institute for Social Research, University of Michigan, 2016).…”
Section: Challenges Of Studying Older Adults’ Internet Usesmentioning
confidence: 99%
“…At all quantile levels discussed in this study, Internet usage can weaken the association between high income and less depressive symptoms, which means that individuals suffering income-related disparity of depression can relieve the symptoms via digital technology. Thus, SES or health disadvantaged groups can obtain better mental health outcomes via digital technology usage [16,20,33,36,38,47].…”
Section: Main Findingsmentioning
confidence: 99%